ANALISIS PEMANFAATAN BAHAN ALAM SEBAGAI MEDIA PEMBELAJARAN MENINGKATKAN KREATIVITAS ANAK TK ISLAMIYAH PONTIANAK - Sari, Rini; Ali, Muhammad; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakThis study aims to determine utilization of natural materials as a learning media to increase creativity in children aged 5-6 years in Islamiyah Kindergarten Pontianak. The research method used is descriptive with qualitative research forms. The data source of this study included 2 teachers and children from B2 group, totaling 15 people, consisting of 7 boys and 8 girls. The class teacher as the main informant in obtaining data. For the data using observations for learning activities, and the results of interviews with classroom teachers and documentation of the results of learning activities and planning learning. The results of research on learning planning are the teacher determines the theme, prepares the media. The implementation of learning is done after planning is made. The development of children's creativity has increased, namely there are children who are actively asking questions and happy in doing learning activities. Constraints in learning are the allocation of less time, the media is hard to get, and there are children who are busy themselves. The efforts made by the teacher in learning activities are creating interesting activities, and adjusting the available time allocation, as well as finding and using the media in the surrounding environment. As for the suggestions in this study, namely the input and knowledge for researchers in the future, for teachers, it is better to allocate more time to activities and vary the media used, as well as for institutions to tighten school rules.Keywords: Instructional Media, Natural Materials, and Creativity